Diagnóstico do uso e ocupação do solo na bacia hidrográfica do Rio São José, Cascavel PR. - Gois, José Francisco de (2008)
The use of soil is understood as a space that is being occupied by man, developing a set of activities of production and reproduction of a society, involving both urban and agricultural areas. Due to the economic development of the last few years, this subject has been studied more and more with a common concern: the quality of water. The objective of this paper is based on the elaboration of a diagnosis of the use and occupation of the soil of the São José river basin, in the city of Cascavel, PR, as a subsidy for the evaluation of the landscape, serving as a tool to the management and adequacy of the area for captation of water to human consumption. This study is of great importance, since the area is considered potential future supplying source for the city of Cascavel Pr. No study of the characterization of this hydrographic basin has been carried out so far. Satellite pictures and topographical letters of the area have been used and geoprocessing techniques provided by softwares ArcView and Spring have also been used. Initially, it was carried out the delimitation of the basin, the geomorphologic characterization of the physical factors of the use of the soil and types. The total area of the hydrographic basin is of 143,8 km ². The characteristics and physical indicators of the basin had demonstrated that the studied area presents a dense net of draining with great trend for peaks of overflow. The area presents six geomorphologic types: steep hillsides very soft and plains to alluvial (11%), hillsides (10.9%), very soft hillsides with rectilinear and irregular sources (34.8%), intermediate hillsides with irregular sources (14.8%), steep hillsides (28.9%) and areas of tops of mount (2.1%), all with formations of The Podzolic Latosol and the basalt presence. As to the definition and characterization of the uses of the soil of the basin it was evidenced the existence of five classes: areas of pastures (31.3%), temporary culture (43.5%), which are the predominant types of use, urban activity (1.7%), areas with intense administrative activity in the country property (1.7%) and forest-covered areas (21.6%). With these data, a comparative analysis was build up to compare the classes of use of the soil versus Geomorphology, where it has been verified that the developed activities can jeopardize the quality of the water, therefore maximize the geomorphologic degradation. For the relation Classes of Use of the soil versus Declivity it was verified that where there are areas of bigger declivity there are activities that are not compatible with it, requiring replanning. In the comparison of the Use of the soil with Law number 4771 of 1965, of the Brazilian Forest Code, it was evidenced that the areas of permanent preservation are very degraded, being invaded for the cattle raising activity and temporary culture, increasing the sand accumulation in the riverbed. In such way, as the hydrographic basin is potential future supplying source for human use, there is a need of monitoring and replanning the activities as well as the elaboration of projects that recover the ciliar bush, so that it prevents the sand accumulation of the hydric courses, and guarantees the quality of water, making it possible consumption of water in a safe way.